The Influence of Population and Economic Growth on Capital Expenditures through Original Regional Income of East Kalimantan Province 2018-2022 - Zakiah; Muhammad Awaluddin; Diana Lestari (International Journal of Sustainable Applied Sciences, 2024)
Understanding the degree of regional autonomy in funding development and government operations by raising the possibility of regional revenue is a crucial component of putting regional autonomy authority into practice. The degree of regional financial independence indicates how well the regional government has been able to boost local financial capability and lessen reliance on financial aid from the federal government. In order to determine the direct and indirect impacts between variables, this study used the route analysis data analysis method (route Analysis) with SPSS (Statistical Product and Service Solutions) software version 29. Path analysis is chosen in this study because it enables testing of the theoretical applicability of the methodology employed, which is the causal relationship approach. Path analysis is a useful tool for analyzing more complex models than multiple linear regression can handle. The government is projected to be able to implement strategic policy initiatives in an effort to raise Regional Original Income, which serves as a source of funding for capital expenditures.